2010
DOI: 10.1097/jcp.0b013e3181fc343b
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Patients' Perceptions During Treatment and Early Discontinuation of Serotonin Selective Reuptake Inhibitor Antidepressants

Abstract: Studies have suggested that discontinuation of treatment in depressed patients is associated with their perceptions about their treatment. We surveyed 403 adults treated for major depressive disorder with a selective serotonin reuptake inhibitor (SSRI) 3 months after onset of treatment to assess their interactions with clinicians, reasons they stopped SSRI treatment, and SSRI side effects (SEs). Bothersome SEs, poorer instruction by physicians about SSRI SEs, and self-reported change in depression, sex, marita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
(20 reference statements)
1
35
1
1
Order By: Relevance
“…12,[32][33][34] We also found that patients living in neighborhoods with lower levels of education had lower rates of antidepressant adherence, and although some studies found similar results, 28,34 others did not find education to have an effect. 29,30,35 In our population, patients with higher comorbidity burden were more likely to adhere to their antidepressant medications, perhaps due to a learning effect, having a routine for consistently taking medications, or having a better understanding of the negative effects of stopping chronic disease medications. Other studies have found mixed effects for the impact of disease burden on medication adherence, with some finding improved adherence in patients with greater comorbidity, 36,37 and others finding no effect or decreased adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,[32][33][34] We also found that patients living in neighborhoods with lower levels of education had lower rates of antidepressant adherence, and although some studies found similar results, 28,34 others did not find education to have an effect. 29,30,35 In our population, patients with higher comorbidity burden were more likely to adhere to their antidepressant medications, perhaps due to a learning effect, having a routine for consistently taking medications, or having a better understanding of the negative effects of stopping chronic disease medications. Other studies have found mixed effects for the impact of disease burden on medication adherence, with some finding improved adherence in patients with greater comorbidity, 36,37 and others finding no effect or decreased adherence.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, only four of the 32 studies analyzed the effects of race on adherence, and three of these were fairly small, with sample sizes between 390 and 403, and reliant on self-reports of adherence. [28][29][30] Two studies found no differences between racial/ethnic groups, but their minority patient samples were fairly small, at 134 and 143 patients each. 29,30 The third study found that Hispanic patients were less adherent than non-Hispanic white patients (OR=0.58, 95% CI: 0.36 to 0.94), while adherence rates for blacks and an "other" racial/ethnic group were similar to non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, data on convergent/discriminant validity are needed to better delimitate the proposed constructs. Finally, existing evidence about the predictive performance of measures of SDM on behavioral (adherence, self-management) and health outcomes (symptoms, health-related quality of life) is scarce, but some significant positive associations have been found (Loh, Simon, et al 2007;Clever et al 2006;Woolley et al 2010). The significant impact that mental health problems have on distinct life areas also highlight the importance of patients' social support, and in this sense the involvement of caregivers, family, or parents of young patients in the process of care and decision making seems crucial to increases the quality of services and maximize clinical improvement and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This activity addressed a number of factors in the doctor-patient relationship and prescribing process that are IoM priorities and which are known to enhance pharmacologic treatment outcomes. These factors include involvement in medical decision making, [32][33][34] good communication, [35][36][37] and providing information about side effects. 26 There are a number of potential limitations with regard to this research.…”
Section: Discussionmentioning
confidence: 99%